Fluorobenzoic acid coformers to improve the solubility and permeability of the BCS class IV drug naftopidil - Mannava, M. K. Chaitanya; Bommaka, Manish K.; Dandela, Rambabu; Solomon, K. Anand; Nangia, Ashwini K. (Chemical Communications, 2022)
Crystalline salts of the low solubility and low permeability drug naftopidil were investigated with mono-, di-, tri-, and tetrafluorobenzoic acids as coformers to show that 245TFBA (2,4,5-trifluorobenzoic acid) is the optimal salt with faster dissolution and high permeability, thereby opening the study of fluorinated coformers in pharmaceutical cocrystals and salts.